Opening the doors a crack wider: palliative care research data in the public domain. Issue 1 (18th January 2016) - Lindqvist, Olav; Rasmussen, Birgit H; Fürst, Carl Johan; Tishelman, Carol
Abstract : This report builds further on OPCARE9, an EU 7th framework project aiming to identify knowledge gaps in care provision in the last days of life. This study began with curiosity about new ways of generating research questions to meet future challenges in palliative care (PC) and how to better engage disciplines not generally included in PC research. We here describe an innovative methodological approach to generating data; put data relevant for PC research in the public domain; and raise issues about open access in PC research. We aimed to compile research questions from different disciplines, based on raw data consisting of approximately 1000 descriptions of non-pharmacological caregiving activities (NPCAs), generated through previous research. 53 researchers from different fields were sent the full list of NPCAs and asked to generate research questions from their disciplinary perspective. Responses were received from 32 researchers from 9 countries, generating approximately 170 research topics, questions, reflections and ideas, from a wide variety of perspectives, which are presented here. Through these data, issues related to death and dying are addressed in several ways, in line with a new public health approach. By engaging a broader group of disciplines and facilitating availability of data in the public domain, we hope to stimulate more open dialogue about a wider variety of issues related to death and dying. We also introduce an innovative methodological approach to data generation, which resulted in a response rate at least equivalent to that in our Delphi survey of professionals in OPCARE9.